2000
DOI: 10.1007/s004269900006
|View full text |Cite
|
Sign up to set email alerts
|

Strategy application disorder: the role of the frontal lobes in human multitasking

Abstract: Strategy application disorder is a term used to describe a pattern of deficits, usually associated with frontal lobe dysfunction, where people show disorganisation, absentmindedness and problems with planning and decision making in everyday life despite normal performance on traditional neuropsychological tests. It is argued that the prototypical situation which presents problems for these cases are those which require multitasking, and although good cases are rare in the literature, those that do exist show a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

20
224
1
12

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 331 publications
(257 citation statements)
references
References 45 publications
20
224
1
12
Order By: Relevance
“…Burgess (2000aBurgess ( , 2000bShallice & Burgess, 1991) has shown that multitasking is sensitive to the impact of frontal lobe damage in adults, even in cases where standard tests of EF are not. This suggests that multitasking paradigms might have a greater sensitivity for detecting EF difficulties, which would be beneficial when assessing clinical populations.…”
Section: Introductionmentioning
confidence: 99%
“…Burgess (2000aBurgess ( , 2000bShallice & Burgess, 1991) has shown that multitasking is sensitive to the impact of frontal lobe damage in adults, even in cases where standard tests of EF are not. This suggests that multitasking paradigms might have a greater sensitivity for detecting EF difficulties, which would be beneficial when assessing clinical populations.…”
Section: Introductionmentioning
confidence: 99%
“…TBI is typically acquired as the result of falls or traffic accidents and predominantly implicates prefrontal cortex structures of the brain (Bigler, 2001;Taber et al, 2006). Accordingly, TBI often has little effect on measured intellectual ability or long term memory (Burgess, 2000), yet results in impaired executive functions, characterized by poor decision making and difficulty in planning and organizing daily activities (Wood 2001;Baddeley, 2002). Note that other AGL researchers have employed patient populations, but never before has a TBI sample been used in the context of AGL or the implicit-explicit distinction (Knowlton & Squire, 1994Smith & McDowall, 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Burgess (2000) has provided a detailed description of the features involved in this kind of multitasking situation, prototypical examples of which are cooking a meal, or carrying out a range of errands in a shopping centre. Multitasking has so far been studied in the neuropsychological literature by contrasting the performance of brain lesioned patients with that of matched controls, on tests designed to tap similar cognitive processes to those involved in real life multitasking.…”
Section: Introductionmentioning
confidence: 99%
“…Interruptions were one of the features identified by Burgess (2000) as characteristic of a multitasking situation. Despite this, studies that have examined the multitasking deficits of patients, have not tested the ability of patients to deal with externally imposed interruptions during these kinds of tests.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation